AGS Position Statement: Making Medical Treatment Decisions for Unbefriended Older Adults. Issue 1 (22nd November 2016) - Farrell, Timothy W.; Widera, Eric; Rosenberg, Lisa; Rubin, Craig D.; Naik, Aanand D.; Braun, Ursula; Torke, Alexia; Li, Ina; Vitale, Caroline; Shega, Joseph; ,
Abstract : In this position statement, we define unbefriended older adults as patients who: (1) lack decisional capacity to provide informed consent to the medical treatment at hand; (2) have not executed an advance directive that addresses the medical treatment at hand and lack capacity to do so; and (3) lack family, friends or a legally authorized surrogate to assist in the medical decision‐making process. Given the vulnerable nature of this population, clinicians, health care teams, ethics committees and other stakeholders working with unbefriended older adults must be diligent when formulating treatment decisions on their behalf. The process of arriving at a treatment decision for an unbefriended older adult should be conducted according to standards of procedural fairness and include capacity assessment, a search for potentially unidentified surrogate decision makers (including non‐traditional surrogates) and a team‐based effort to ascertain the unbefriended older adult's preferences by synthesizing all available evidence. A concerted national effort is needed to help reduce the significant state‐to‐state variability in legal approaches to unbefriended patients. Proactive efforts are also needed to identify older adults, including "adult orphans, " at risk for becoming unbefriended and to develop alternative approaches to medical decision making for unbefriended older adults. This document updates the 1996 AGS position statement on unbefriended older adults.